Implementation of Realistic Mathematics Education and Project-Based Learning to Improve Students' Mathematical Thinking Ability and Empathy Skills - Afifah, Nur; Isyati, Andini Norma; Pratama, Loviga Denny (Jurusan Pendidikan Matematika FKIP Universitas Halu Oleo, 2025)
The ability to think mathematically is an important aspect in learning mathematics, but many students still experience problems in understanding abstract concepts such as sets and show a lack of empathy in group work, as found. This research aims to improve students' mathematical thinking skills and empathy through the Realistic Mathematics Education approach combined with the Project-Based Learning model. The method used was classroom action research carried out in two cycles in class VIII with 15 students as research subjects. The research procedure refers to Kemmis and McTaggart's spiral model, which consists of planning, implementation, observation and reflection phases. Data collection was carried out through mathematical thinking ability tests, observation of student activities, and empathy questionnaires. The results show that at the initial stage, there were no students who met the Minimum Completeness Criteria (KKM), and the level of empathy was relatively low. After implementing the learning strategy, there was a significant improvement in both aspects, especially in the second cycle. These findings indicate that the integration of the RME approach and the PjBL model is effective in developing mathematical thinking skills and increasing student empathy in learning mathematics